Case report: acute facial swelling in a recreational technical diver - Buzzacott, Peter; Dolen, W.; Chimiak, J. (2017)
© 2017 The Authors. Physiological Reports published by Wiley Periodicals, Inc. on behalf of The Physiological Society and the American Physiological Society. A recreational scuba diver wore a second scuba regulator against his face during a scuba dive, attached by an elastic rubber cord necklace. After surfacing, the diver's left face became swollen. Through a process of elimination all other items of scuba equipment were excluded as potential causes. A dive with the same equipment minus the necklace confirmed the involvement of the necklace in the pathogenesis of the hypersensitive reaction. In vitro ImmunoCap IgE assay was positive to latex (1.30 kUa/L), subsequent patch testing for contact dermatitis provoked a reaction for benzophenone-4, (a UV stabalizer) and Fourier Transform Infra Red spectroscopy identified the elastic as ethylene propylene rubber, containing additional unidentified compounds. Allergy to natural rubber latex occurs in as many as 6% of Americans and Australians. Around three million American residents are thought to scuba dive each year. Recreational divers are, therefore, advised to check such necklaces, which are typically worn around the throat, for frayed ends and exposed rubber filaments.